2021
DOI: 10.1111/pere.12377
|View full text |Cite
|
Sign up to set email alerts
|

Quality of alternatives positively associated with interest in opening up a relationship

Abstract: We use the Investment Model framework to examine what relationship features are associated with interest in and positive evaluations of consensual non‐monogamy (CNM) among individuals in monogamous relationships. In data sets from the United States (Study 1), Europe (Study 2), and Korea (Study 3; total N = 886), perceptions of higher‐quality alternatives were consistently associated with more interest in CNM. Further, consistent with previous work on commitment‐motivated relationship maintenance processes, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Given that people’s evaluation of their relationship is greatly influenced by the quality of their alternatives and the extent to which they perceive them to be more or less desirable than their current partner (Le & Agnew, 2003; Lydon et al, 1999; Rusbult, 1983), these processes that downgrade the appeal of alternatives are powerful relationship maintenance tools. Indeed, social comparison processes are activated when people are confronted with an attractive alternative to their current romantic partner, threatening their relationship satisfaction (Rusbult, 1983) and rendering other options potentially more appealing (MacDonald et al, 2021). To the extent that people continue to ignore alternatives or view them as less appealing, their current romantic partner will remain the better and more appealing option, supporting relationship longevity.…”
Section: The Threat Of Attractive Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that people’s evaluation of their relationship is greatly influenced by the quality of their alternatives and the extent to which they perceive them to be more or less desirable than their current partner (Le & Agnew, 2003; Lydon et al, 1999; Rusbult, 1983), these processes that downgrade the appeal of alternatives are powerful relationship maintenance tools. Indeed, social comparison processes are activated when people are confronted with an attractive alternative to their current romantic partner, threatening their relationship satisfaction (Rusbult, 1983) and rendering other options potentially more appealing (MacDonald et al, 2021). To the extent that people continue to ignore alternatives or view them as less appealing, their current romantic partner will remain the better and more appealing option, supporting relationship longevity.…”
Section: The Threat Of Attractive Alternativesmentioning
confidence: 99%
“…As social exchange and interdependence theory suggest (Levinger, 1979; Rusbult, 1983), relational stability and satisfaction are greatly influenced by the subjective evaluation of one’s own relationship “reward” and “costs” compared to those that could be obtained through other possible relationships (e.g., Amato & Hohmann-Marriott, 2007; Levinger, 1979). According to these perspectives, the positive and negative outcomes associated with the current relationship provide valuable information that motivates people to make an important relationship relevant choice, and having good alternatives is one of the strongest reasons to change the relationship one is currently in (e.g., transforming a monogamous relationship to a consensually nonmonogamous one; MacDonald et al, 2021) or leave the relationship altogether (Machia & Ogolsky, 2021). Importantly, the evaluative process that people go through when making these relationship decisions and evaluating its costs and benefits is a turbulent one (Joel et al, 2021), as it likely brings saliency to the conflicting emotions present in the relationship, highlighting and exacerbating preexisting feelings of ambivalence toward their current romantic partner.…”
Section: The Threat Of Attractive Alternativesmentioning
confidence: 99%
“…Most of these studies ( n = 147; 70.33%) were conducted in North America; others were conducted in Europe ( n = 46; 22.01%), Australia/New Zealand ( n = 8; 3.83%), Asia ( n = 1), and South America ( n = 1). A few studies ( n = 6; 2.87%) had participants from multiple continents (e.g., Cubells‐Serra et al, 2021; MacDonald et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding personality correlates, people who had more active imaginations, a preference for variety and change, and a proclivity to engage in new experiences (i.e., high in openness) reported a greater desire to engage in CNM than those who were very organized, and neat, careful, and self‐disciplined (i.e., high in conscientiousness) (Flicker & Sancier‐Barbosa, 2022; Moors, Matsick, & Schechinger, 2017; Moors, Selterman, & Conley, 2017). Individuals in monogamous relationships who had stronger perceptions of available romantic alternatives were more attracted to CNM than those who perceived fewer alternatives (MacDonald et al, 2021). For young adult women, the indirect, positive association between perceiving young adulthood as a time of experimentation/possibilities and willingness to engage in CNM was mediated by sexual identity exploration (Sizemore & Olmstead, 2017b).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies have found no gender differences or have found gender irrelevant to the prediction of CNM attitudes [41,45,47,54,60,65,71,74,[76][77][78][79][80]. Most of these studies used vignette assessments, while some used aggregate scales.…”
Section: Gendermentioning
confidence: 99%